Pasta modern : new & inspired recipes from Italy - Segan, Francine (New York : Stewart, Tabori & Chang, 2013)
Offers one hundred illustrated recipes for unusual and innovative Italian pasta dishes, covering appetizers, soups, main dishes, and desserts.
Includes index.
Keywords: Cooking (Pasta); Cooking, Italian; Cooking -- Pasta; Italian cooking; Cookbooks